2017
DOI: 10.1055/s-0037-1615280
|View full text |Cite
|
Sign up to set email alerts
|

Otoplasty Online Information: A Comprehensive Analysis of the Websites and Videos that Patients View Regarding Cosmetic Ear Surgery

Abstract: Physicians should be aware of both websites and videos available online regarding the otoplasty procedure to provide quality care. This study systematically analyzes the authorships, reliability, quality, and readability of the websites, as well as the authorships and primary objectives of the videos regarding otoplasty. Validated instruments were used to analyze the reliability, quality, and readability of websites, and videos were systematically categorized and analyzed. A Google search was conducted, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…Intriguingly, they concluded that physician-associated websites were the least reliable source of information, whereas unaffiliated websites were with the most reliable information for the patients who are seeking knowledge about otoplasty. Besides, the academic websites were with the highest quality of information, but the patient-mediated websites were with the lowest quality 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intriguingly, they concluded that physician-associated websites were the least reliable source of information, whereas unaffiliated websites were with the most reliable information for the patients who are seeking knowledge about otoplasty. Besides, the academic websites were with the highest quality of information, but the patient-mediated websites were with the lowest quality 20 …”
Section: Discussionmentioning
confidence: 99%
“…16,17 They also stated that the reliability of these videos was inconsistent depending on the specialties and video sources. 18,19 Nissan et al 20 conducted a study to evaluate the view of the patients about otoplasty procedure. They reviewed websites and the first 50 relevant videos presenting information regarding otoplasty from the patients' perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 43 studies investigating SM use for patient education, 16 analyzed the composition and quality of videos on YouTube, a popular open-source video-sharing platform, for various otolaryngological procedures and conditions. Clinical contexts included education regarding vestibular schwannoma, laryngeal cancer and laryngectomy, cochlear implantation, pediatric tonsillectomy, and rhinoplasty 22,25,96,[108][109][110]167,168,[171][172][173] ; online portrayal of hearing loss and hearing aid use 6,101 ; and instructional videos on "how to stop a nosebleed" and "how to use nasal sprays". 67,170 Several studies utilized the Discern instrument, a validated tool used to judge the quality and assess the reliability of published medical information, 177 and in general, found significant variability in quality and reliability of videos.…”
Section: Patient Educationmentioning
confidence: 99%
“…Die meisten vorangegangenen Arbeiten kategorisierten die untersuchten Webseiten nicht nach den Urhebern. Eine Studie von Nissan et al [42] unterteilte die Urheber in 4 Autorenkategorien: Arzt, Patient, akademisch oder nicht zuzuordnen. Eine andere Arbeit von San Georgi et al [39] [20].…”
Section: Beeinflussende Faktorenunclassified
“…In der vorliegenden Analyse zeigte sich eine mäßiggradige Bewertung. Vorangegangene Studien zu anderen Themen wiesen ähnliche DISCERN-Ergebnisse [20,40] oder sogar schlechtere [20,42] auf. Ein HON-Zertifikat zeigte sich bei 0-30,6 % der in vorausgegangenen Studien analysierten Internetseiten zu HNO-Themen [20,40,41,43,44].…”
Section: Beeinflussende Faktorenunclassified